Design of T cell receptor libraries with diverse binding properties to examine adoptive T cell responses - Chervin, A.S. (Gene Ther, 2012)
Adoptive T cell therapies have shown significant promise in the treatment of cancer and viral diseases. One approach, that introduces antigen-specific T cell receptors (TCRs) into ex vivo activated T cells, is designed to overcome central tolerance mechanisms that prevent responses by endogenous T cell repertoires. Studies have suggested that use of higher affinity TCRs against class I MHC antigens could drive the activity of both CD4(+) and CD8(+) T cells, but the rules that govern the TCR binding optimal for in vivo activity are unknown. Here we describe a high-throughput platform of “reverse biochemistry” whereby a library of TCRs with a wide range of binding properties to the same antigen is introduced into T cells and adoptively transferred into mice with antigen-positive tumors. Extraction of RNA from tumor-infiltrating lymphocytes or lymphoid organs allowed high-throughput sequencing to determine which TCRs were selected in vivo. The results showed that CD8(+) T cells expressing the highest affinity TCR variants were deleted in both the tumor infiltrating lymphocyte population and in peripheral lymphoid tissues. In contrast, these same high-affinity TCR variants were preferentially expressed within CD4(+) T cells in the tumor, suggesting they played a role in antigen-specific tumor control. The findings thus revealed that the affinity of the transduced TCRs controlled the survival and tumor infiltration of the transferred T cells. Accordingly, the TCR library strategy enables rapid assessment of TCR binding properties that promote peripheral T cell survival and tumor elimination.